APLIKASI CYBER COUNSELING-NGOBROL YUK BERBASIS ANDROID (WHATSAPP) UNTUK MENINGKATKAN PSYCHOLOGICAL WELL-BEING SISWA SEKOLAH DASAR - Kristina Betty Artati; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to make it easier for counseling teachers to describe a model of online counseling services. BK teachers are required to be able to provide good and best service through the guidance and counseling process. Developments in Information and Communication Technology (ICT) can be utilized in cyber counseling and handling various services, currently almost all students have cellphones which on average can be used to build systems by optimizing cyber counseling applications based on Android (whatsapp) to improve psychological well-being of elementary school students. The development of communication in the era of digital technology helps provide counseling services more broadly. In the digital era, counseling is not only in the form of face-to-face meetings, but it can be done using the internet network with several applications such as Facebook, Twitter, Instagram, WhatsApp and various other types of applications. This counseling model is also called cyber counseling. This research method is a descriptive method, which aims to obtain an overview of the object of research. Retrieval of data by giving questionnaires to students about student responses to the application of online counseling which consists of two choices (yes / no). To determine the results of student responses to the implementation of online counseling, statistical analysis using presentation techniques was used. The effectiveness of this counseling is measured from student responses which are proven that students feel comfortable, relieved, easy to use the application, helped to solve the problems they face, and Back motivated to continue to achieve goals. Therefore, the cyber counseling-chat application based on Android (whatsapp) to improve students' psychological well-being should be used as a model for counseling services for elementary school students in the digital era effectively.